2001
DOI: 10.1046/j.0014-2956.2001.02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of endothelin receptors to the ERK/MAP kinase pathway

Abstract: Endothelins are potent mitogens that stimulate extracellular signal-regulated kinases (ERK/MAP kinases) through their cognate G-protein-coupled receptors, ET A and ET B . To address the role of post-translational ET receptor modifications such as acylation on ERK activation and to identify relevant downstream effectors coupling the ET receptor to the ERK signaling cascades we have constructed a panel of palmitoylation-deficient ET receptor mutants with differential Ga protein binding capacity. Endothelin-1 sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 64 publications
2
51
0
Order By: Relevance
“…For example, the ␤ 2 -adrenergic receptor (AR) is palmitoylated at Cys 341 , and palmitoylation at this site is required for ␤ 2 -AR coupling to adenylyl cyclase (9) and is increased upon exposure of cells to agonist (10). Palmitoylation of the endothelin (ET) A and ET B receptors is required for their coupling to the extracellular signal regulated kinase/ mitogen-activated protein kinase cascade (11). Mutation of Cys 442 within the C-tail of the ␣ 2A -AR receptor inhibits receptor down-regulation in response to prolonged agonist exposure (12).…”
Section: Superfamily (1 2 4 5)mentioning
confidence: 99%
“…For example, the ␤ 2 -adrenergic receptor (AR) is palmitoylated at Cys 341 , and palmitoylation at this site is required for ␤ 2 -AR coupling to adenylyl cyclase (9) and is increased upon exposure of cells to agonist (10). Palmitoylation of the endothelin (ET) A and ET B receptors is required for their coupling to the extracellular signal regulated kinase/ mitogen-activated protein kinase cascade (11). Mutation of Cys 442 within the C-tail of the ␣ 2A -AR receptor inhibits receptor down-regulation in response to prolonged agonist exposure (12).…”
Section: Superfamily (1 2 4 5)mentioning
confidence: 99%
“…Knock-in of Ednrb cDNA could only partially rescue the Ednra-null phenotype Previous studies have demonstrated that Edn1 can bind to both Ednra and Ednrb receptors with similar affinities and activate common signaling pathways, including G q /G 11 -dependent signals in many cells (Cramer et al, 2001;Jouneaux et al, 1994;Kedzierski and Yanagisawa, 2001;Masaki et al, 1999;Takigawa et al, 1995). If Ednra and Ednrb are interchangeable in the context of pharyngeal arch development, Ednrb knock-in is expected to rescue the Ednranull phenotype.…”
Section: Fig 2 Rmce-mediated Knock-in Of Lacz Into the Ednra Locusmentioning
confidence: 99%
“…Coupling of ET-1 receptors to G␣q could lead to activation of phospholipase C and hence PKC (8,31,32). The results of PKC inhibition experiments using bisindolylmaleimide I suggested involvement of a novel PKC subtype ( Figure 6A), and the lack of effect of Rottlerin highlighted a possible role of PKC ( Figure 6B).…”
Section: Discussionmentioning
confidence: 92%